Review article of Sidhma kushtha (Psoriasis) (International Journal of Food and Nutritional Sciences, 2022)
The present paper is based on Ayurvedic disease “Sidhma kushtha.” Here we can compare it modern skin disease “Psoriasis”. Psoriasis is one of the most common dermatological diseases, affecting up to 1 to 2 percent of the world’s population. In India the incidence is approaching 1%, which is less than that in European countries. It occurs in all age groups and about equally in men and women. The etiology of psoriasis is still poorly understood, but there is clearly a genetic component. It has been found in large surveys that one-third of patients have a positive family history. Evidence has accumulated, clearly indicating a role for T- cells in the pathophysiology of psoriasis. Psychological aspect of psoriasis is most important in the etio-pathogenesis and management of psoriasis. There are many references for Ayurvedic management of Sidhma kushtha that we have to apply in modern time. Finally main intention for presenting this paper is to share basic details of Sidhma Kushtha for proper Treatment.